Management of radiation-related supraglottic stenosis with serial in-office steroid injections - Kim, Christine M.; Patel, Pratik B.; Feinstein, Aaron J.; Chhetri, Dinesh K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Management of supraglottic stenosis in patients with history of head and neck radiation presents a clinical challenge for otolaryngologists. The cornerstone of treatment has historically been surgical intervention, both endoscopic and open. However, recently described techniques related to outpatient management of subglottic and tracheal stenosis with routine in-office steroid injections may provide a translatable model for supraglottic stenosis management. We describe a clinical protocol for in-office steroid injections to the laryngopharynx for patients with supraglottic stenosis secondary to radiation fibrosis. Two patient cases are reported, including endoscopic examinations over a follow-up period of 12 to 16 months. Both patients experienced significant improvement in their supraglottic airways. In-office steroid injections may be beneficial to prevent or slow stenosis recurrence in patients treated with radiation for head and neck cancer. With continued refinement of this technique, a paradigm shift may occur in the management of supraglottic stenosis.